2022
DOI: 10.3390/jmmp6010012
|View full text |Cite
|
Sign up to set email alerts
|

Wind Tunnel Experiments on an Aircraft Model Fabricated Using a 3D Printing Technique

Abstract: Experimental tests regarding the M-346 aircraft model made via 3D printing were carried out in order to obtain numerical data and characteristics in the form of graphs of basic aerodynamic forces and coefficients. The tests were carried out for the left side of the airframe model in a clean configuration, without additional suspension equipment; the flight control surfaces and the aerodynamic brake were in neutral positions. Based on the scan of the base model in 1:48 scale using a Nikon Model Maker MMDx laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Three-dimensional printing is a key tool for manufacturing precise and high-quality aerodynamic models [28]. It allows for rapid manufacturing of prototypes, which accelerates the design and testing process [29].The tested aerodynamic airfoils were manufactured using PLA (polylactic acid), a biodegradable polymer. The equipment used for manufacturing was an Ultimaker 3S 3D printer, and the prototypes were designed using 3D generation modeling software (CATIA, Dassault Systèmes).…”
Section: • Particle Image Velocity In Airmentioning
confidence: 99%
“…Three-dimensional printing is a key tool for manufacturing precise and high-quality aerodynamic models [28]. It allows for rapid manufacturing of prototypes, which accelerates the design and testing process [29].The tested aerodynamic airfoils were manufactured using PLA (polylactic acid), a biodegradable polymer. The equipment used for manufacturing was an Ultimaker 3S 3D printer, and the prototypes were designed using 3D generation modeling software (CATIA, Dassault Systèmes).…”
Section: • Particle Image Velocity In Airmentioning
confidence: 99%
“…These coefficients are frequently used to show how the lift-to-drag ratio changes depending on the angle of attack. With speed, the angle of attack varies depending on the lift's specific magnitude [28]. A wing moves through the air at an angle to the direction of flight.…”
Section: Proceedings Of the 8 Th International Exchange And Innovatio...mentioning
confidence: 99%
“…They concluded that the FDM process offered both structural and aerodynamic advantages for the manufacturing and testing of small UAV models. Szwedziak et al [20] experimentally investigated the M-346 aircraft in a wind tunnel using a model produced with the FDM process and they reported that the FDM model produced acceptable results.…”
Section: Introductionmentioning
confidence: 99%